The Algorithmic Path to Precision: How AI is Revolutionizing Melanoma Staging - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Melanoma, the most aggressive form of skin cancer, presents a significant global health challenge. Accurate and timely staging is a critical determinant of t...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine